Does Entitlement Card ensure Utilization of Urban Primary Healthcare Clinic in Bangladesh? - Mizan, Sharmin; Rahman, Md Mizanur; Safii, Razitasham binti; Ahmad, Sk Akhtar (Journal of Maternal and Child Health, 2020)
Background: Although Bangladesh substantially reduced 40% maternal death in the last decades, it is still challenging, especially among the urban poor. The achievements are not equitable between different economic quintiles and between the rich and the urban poor. This study aims to examine the extent to which the entitlement card affects the utilization of maternal and child health care and identifies other factors that influence MCH services.Subjects and Method: This cross-sectional study was carried out in the working areas of the Urban Primary Healthcare Project (UPHCP) in Bangladesh. A two-stage cluster sampling technique was used to select the participants. A total of 3,949 women aged 15-49 years, having at least one child aged two years or less were selected for this study. The data were collected through face-to-face interviews. The data were analyzed using multinomial logistic regression.Results: The proportion of utilization of UPHCC was 49.9%. One-fourth (26.6%) of them fully utilized it and another 23.3% utilized it partially. Stepwise multinomial logistic regression analysis revealed that those who had an Entitlement Card from the UPHC project were 11.75 times (95% CI= 9.481, 14.549; p= 0.001) more likely to fully Utilized and 3.64 times (95% CI= 3.643, 2.911; p= 0.001) likely be utilized partially compared to non-utilizer. Respondents having no formal education utilized UPHCC fully (AOR=2.32; 95% CI= 1.46, 3.68; p= 0.001) and partially (AOR= 1.76; 95% CI= 1.12, 2.77; p= 0.014) used UPHCC. It was 3.08 (95% CI= 2.03, 4.67; p= 0.001) times for fully and 2.71 (95% CI= 1.82, 4.04; p= 0.001) times for partially utilized UPHCC compared to non-users among the primary level of education. Small family size (≤4) and monthly family income in the range of BDT 10,000 above were likely to utilise UPHCC. However, non-Muslims were less likely to Utilized UPHCC.Conclusion: Apart from the entitlement card, other factors such as monthly income BDT> 10,000, small family size, no formal educated mother appeared to be potential predictors for utilization of the Urban Primary Health care clinic.Keywords: entitlement card, maternal care, Utilization, urban primary healthcareCorrespondence: Md Mizanur Rahman. Department of Community Medicine and Public Health, Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak. Email: rmmizanur@unimas.my, rmizanur1958@gmail.com.Journal of Maternal and Child Health (2020), 5(2): 213-225https://doi.org/10.26911/thejmch.2020.05.02.12